Conducting Difficult Performance Counseling Sessions - Mary Lou Higgerson (Academic Chairpersons Conference Proceedings, 2016)
Department chairs are responsible for reviewing the performance of individual faculty and staff members. This task can be especially difficult and uncomfortable when a faculty or staff member is not meeting performance expectations. In this session, participants will have the opportunity to learn and practice some specific communication strategies for conducting difficult performance counseling sessions with individuals who are not meeting performance expectations.
Keywords: Conducting Difficult Performance Counseling Sessions